Appendice: Binet e la questione dei titoli lussoriani - ZURLI, Loriano (AL. Rivista di studi di Anthologia Latina, 2021)
Abstract The question of the authenticity of the Luxorian titles is reexamined by relating it to the stemma codicum of Anthologia Latina, now enriched by the acquisitions regarding Binet’s deperditus Bellovacensis. The titles of the poems of Anthologia Latina present in the sixteenth-century edition of Binet are discussed.